2018
DOI: 10.1016/j.toxrep.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Asparagus officinalis extract against Bisphenol A- induced toxicity in Wistar rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Asparagus officinalis (ASP) is a perennial vegetable with remarkable anti-fungal, anti-hepatotoxic, cytotoxic, antimutagenic, anti-inflammatory and diuretic properties (6). The roots and buds of ASP are rich in many bioactive phytochemicals including oligosaccharides, steroidal saponins, amino acid derivatives and essential minerals, which has been used for treatment of various chronic inflammation diseases and cancers in Chinese traditional medicine (6)(7)(8). Polysaccharides, steroidal saponins and flavonoids extracted from ASP have been reported as main bioactive constituents that might have anti-tumor properties (9).…”
Section: Introductionmentioning
confidence: 99%
“…Asparagus officinalis (ASP) is a perennial vegetable with remarkable anti-fungal, anti-hepatotoxic, cytotoxic, antimutagenic, anti-inflammatory and diuretic properties (6). The roots and buds of ASP are rich in many bioactive phytochemicals including oligosaccharides, steroidal saponins, amino acid derivatives and essential minerals, which has been used for treatment of various chronic inflammation diseases and cancers in Chinese traditional medicine (6)(7)(8). Polysaccharides, steroidal saponins and flavonoids extracted from ASP have been reported as main bioactive constituents that might have anti-tumor properties (9).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the serum parameters of kidney function (Cr and BUN) elevated in the iron oxide exposure group; these parameters are considered to be important indicators of kidney damage (27). On the same note, our findings indicated that the serum levels of AST, ALT, ALP, and bilirubin were high in the animals exposed to iron ox-ide since they were sensitive to the liver damage indices due to the cell leakage and loss of the functional integrity of the liver membrane induced by iron intoxication (28).…”
Section: Discussionmentioning
confidence: 75%
“…Asparagaceae family is a nutritious garden vegetable, which is native to most parts of Europe, Africa and Asia consumed throughout the world (Poormoosavi et al, 2018). The consumable shoot of A. officinalis is about 20-35cm in length, which is approximately onehalf to two-thirds of the stem (Zhao et al, 2011) and often used to prepare vegetable dishes, soups and salads (Hafizur et al, 2012).…”
Section: Asparagus Officinalis L (Asparagus) Frommentioning
confidence: 99%
“…The seed extract of this plant also had anti-diabetic (Hafizur et al, 2012) and antifungal (Wang and Ng, 2001) activities. It has been reported root extracts of A. officinalis had beneficial impacts on oogenesis in female rats (Jashni et al, 2016), protective effects against liver and kidney damages (Poormoosavi et al, 2018) and neuroprotective activity in an animal model of neurodegenerative disease (Sakurai et al, 2014). Moreover, A. officinalis juice potentiated cyclophosphamide-induced antimutagenic activities in mice (Xinhui and Jing, 2001).…”
Section: Asparagus Officinalis L (Asparagus) Frommentioning
confidence: 99%